Kepekaan Interkultural sebagai Kecakapan Calon Guru Disertai dengan Faktor Kontekstual dalam Mewujudkan Prinsip Pendidikan Multikultural - Muhamad Uyun (Cendekia, 2022)
Indonesia is one of the countries which has a lot of cultures. Nowadays, multicultural education is very much a provision for students with a high level of intercultural sensitivity. In this case, an educator should has more mastery in intercultural sensitivity to actualize appropriate multicultural education for the future generation. This study aimed to know how the intercultural sensitivity of prospective teachers at UIN Raden Fatah Palembang and IAIN Curup in a quantitative approach. Then, to know how the factors underlie the intercultural sensitivity of prospective teachers in a qualitative approach. The participants in this study were 1000 prospective teachers at UIN Raden Fatah Palembang and 800 prospective teachers at IAIN Curup. The data was collected using a very precise questionnaire to get an accurate percentage toward a level of intercultural sensitivity for prospective teachers. Also, the data is continued with descriptive statistic analysis. The finding revealed that the prospective teachers of UIN Raden Fatah Palembang and IAIN Curup had the same high level of intercultural sensitivity, with the following details: the domain of interaction engagement based on 9 factors, the domain of respect for cultural differences based on 4 factors, the domain of interaction confidence based on 7 factors, the domain of interaction enjoyment based on 5 factors and the domain of interaction attentiveness based on 4 factors.